Synthesis and characterisation of magnetic reduced graphene oxide functionalised by Ganoderma lucidum extract and Pluronic F-127 for delivery of quercetin - Lee, Xin Jie (2018)
Cancer, which is one of the top three causes of worldwide mortality, arises as a result of abnormal and uncontrolled cell growth and the spread of malignant cells. Lung cancer is the most common cancer that has been diagnosed which is associated with high mortality. Herein, a superparamagnetic graphene-based magnetite nanocomposite (rGO-Fe3O4) synthesized via a simple chemical approach, was used as a potential drug delivery carrier for targeted drug delivery that was able to be guided by an external magnetic field. Firstly, the optimization of the nanocomposite synthesis was carried out based on the duration of GO sonication and the weight ratio of GO and Fe3O4. Next, a Ganoderma lucidum (GL) extract was prepared which successfully stabilized the rGO-Fe3O4 via hydrogen bonding and resulted in enhancement of water dispersibility and stability of the nanocomposite. Following this, an amphiphilic polymeric material, Pluronic F-127 (PF) was introduced onto the surface of the rGO-Fe3O4-GL in order to reduce the overall cytotoxicity of the as-synthesized nanocomposite. The as-synthesized nanocomposite was also characterised. Morphological and structural studies were carried out to confirm the deposition of Fe3O4 nanoparticles with an average size of 11.2 nm, on the rGO sheet. Electrochemical studies were performed to validate the presence and successive stabilization and functionalization of both GL and PF by evaluating their electrical conductivity. Lastly, the superparamagnetic property of the nanocomposite was measured and the saturation magnetization of rGOFe3O4- GL-PF obtained was 21.9 emu/g. Quercetin (Que), a naturally-occurring polyphenolic flavonoid with anti-cancer properties, was utilized to study the potential of rGO-Fe3O4-GL-PF for controlled drug delivery applications. The loading capacity of rGO-Fe3O4-GL-PF was 11 wt. % and Que was found to be loaded on the rGO plane via π-π stacking and hydrophobic interactions. The Queloaded rGO-Fe3O4-GL-PF was hypothesized to obey a pH-responsive release mechanism and hence the drug release was studied in both neutral and acidic conditions. As a result, the cumulative percentage obtained for Que release in acidic conditions was 3.68% after 6 hours. However, oxidative degradation of Que occurred upon release in neutral conditions, which revealed that Que was unstable as a drug model in targeted drug delivery studies. The in vitro cytotoxicity of the synthesized nanocomposites was studied using lung fibroblast (MRC-5) and lung carcinoma (A549) cell lines. The rGO-Fe3O4-GL-PF showed an obvious cytotoxicity against the A549 cells as compared to MRC-5 due to the anti-cancer property of the GL extract, which showed its specificity towards cancerous cells only. In addition, the cytotoxicity of the Que-loaded rGO-Fe3O4-GL-PF was investigated, and results indicate a higher cytotoxicity against the A549 cells. Therefore, the as-synthesized rGO-Fe3O4-GL-PF could potentially be developed into a targeted drug carrier for lung cancer therapy by incorporation with different types of chemotherapeutic agents or anti-cancer drugs.